Risco ambiental gerado pelo uso de antibióticos em unidade de saúde: estudo de caso da concentração ambiental prevista - Biselli, Patricia Eduarda (2011)
Emergent contaminants have been recognized as pollutants of superficial water and effluents, especially pharmaceuticals. Among these, antibiotics are the main ones, as much for being widely used in the human and veterinary medicine, as for having biological characteristics of persistence and bioaccumulation that unchain alterations in the aquatic and soil life cycle.The aim of this research was to contribute for the recognition and sizing of this problem. It was conducted and analysis of the environmental risks generated by antibiotics prescribed and excreted in a Unit Health in Curitiba, state of Paraná, from 2006 to 2010. The demographic profile of the population and the basic sanitary conditions were evaluated, the classes and amounts of prescribed antibiotics were raised, which subsidized the evaluation of the excreted volume and the calculation of the Predict Environmental Concentration (PEC). Data of the Predicted Environmental Concentration where no effects are reported (PNEC) and of the removal in sewage system plants by activated sludge and anaerobic treatment were obtained in literature. The Risk Quotient was calculated (QR) by the PEC/PNEC ratio. Out of the twelve identified antibiotics, four presented exclusively high risk (QR> 1): amoxicillin, ampicillin, benzylpenicillin and erythromycina. The Sulfamethoxazole presented high risk in only one year and presented medium risk in the others four years. Metronidazole, trimethoprim and azithromycina presented medium risk (0,1<QR≤1). The cephalosporins, cephalexin, cephuroxime and ceftriaxone presented low risk (0,01<QR≤0,1). For the nitrofurantoin the PEC II varied between 0,0597 and 0,1247 µg/L. The RQ anaerobic removal was high risk for amoxicillin, benzylpenicillin and erythromycin. For penicillins (amoxicillin, ampicillin, benzylpenicillin, erythromycin), sulfamethoxazole, metronidazole, trimethoprim and azithromycin administered, medium and high environmental risk was found. It was identified that the doctor’s background intervenes with the RQ and it was demonstrated that the pattern of antibiotic prescriptions in US offers environmental risks. Future studies related to antibiotic administration, removal technologies in sewage treatment plants, PNEC local studies, awareness of the health professionals, as well as establishment of politics of regulation are recommended.